Adsorption capacity of a hydrogen atom on the 2D silicon carbide surface - Hanh, Tran Thi Thu (Communications in Physics, 2023)
Hydrogen adsorption on two-dimensional (2D) silicon carbide (SiC) was studied using molecular dynamics and ab initio calculations. By investigating a converged density functional theory (DFT) calculation, the stable adsorption sites of a hydrogen atom on the 2D SiC were found at the top sites (TSi and TC, of which the most stable adsorption site is TSi). The adsorption of a hydrogen atom on 2D silicon carbide led to local structural changes in silicon carbide.